LGBTQ young adult fiction : a critical survey, 1970s-2010s - Town, Caren J., 1957- (McFarland & Company, Inc., Publishers, 2017)
"The author explores a selection of recent novels--many of which may be new to readers--and places them in the wider contexts of LGBTQ literature and history. Chapters discuss a range of topics, including the relationship of Queer Theory to literature, LGBTQ families, and recent trends in utopian and dystopian science fiction"- Resumé vydavatel